Progress in the Pipeline: Replication of the Minority Training Program in Cancer Control Research - Yancey, Antronette K. (2006)
BACKGROUND: This paper evaluates the replicability of an NCI-funded didactic/experiential program to increase the diversity of doctorally-prepared cancer disparities investigators. METHODS: The program was developed and operated successfully for three years in Northern California when a replication was established at UCLA. Feasibility, process, impact, and outcome measures on UCSF and UCLA summer-institute participants were compared. RESULTS: Average participant rankings of the influence of the program on intention to apply for a doctorate were 9.1/10 (UCSF) and 8.6/10 (UCLA). A total of 22.5% of UCSF and 10% of UCLA participants have enrolled in, been accepted by, or completed doctoral programs. Among these alumni, 68% (21/31) of UCSF and 60% (3/5) of UCLA participants plan to conduct their doctoral research in cancer control. CONCLUSIONS: This program has been successfully replicated and has met its objective to increase the pipeline of ethnically diverse doctoral-level public health researchers. Expansion of the program to other regions of the US is feasible and indicated.